Microgrid modernization using exponential decentralized consensus-based energy assessment by considering renewable generation uncertainties and operational price analysis - Ijaz Ahmed; Muhammad Rehan; Mohammed Alqahtani; Muhammad Khalid (Results in Engineering)
Modern energy delivery systems depend on two essential pillars: sustainability and resilience. Collectively, these pillars establish a strong framework that guarantees the dependable provision of clean energy while managing constraints associated with energy production and operation. This work investigates a decentralized optimization technique under a directed communication network for decentralized agents to solve the economic dispatch problem (EDP) under uncertain renewable sources via an exponential approach. Exponential incremental cost (IC) consensus and supply-demand equilibrium are used for attaining a fast convergence to an optimal solution. The exponential convergence analysis under directed graphs takes into account a Lyapunov function. The proposed approach considers the uncertainty in renewable sources which has been tackled by incorporating the weather information and by considering grid digitization via smart meters, advanced communication architecture, GPSs-based clock synchronization and cumulative information of generator data. Furthermore, this study introduces renewable energy sources (RESs) into microgrids, highlighting their variability and intermittent nature and accounts for a robust solution for the energy dispatch. Moreover, an assessment for the energy production, emission reduction, and operation cost analysis has also been provided for the eastern part of Saudi Arabia, based on uncertain weather conditions. Simulation testing validates the efficacy of the suggested strategy for an IEEE benchmark networked system. Such an approach can be helpful for the grid modernization, decarbonization, digitization of grid, decentralized solution, energy assessment, and resilience with respect to cyber-attacks.